The Relationship between Knowledge and Attitude about Vulva Hygiene with the Incidence of Vaginal Discharge - Alase, Claudia Pramaisella; Palit, Joan Claudia; Popatoon, Teyza Monica; Ingrit, Belet Lydia; Tahapary, Prisca A. (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Background. Fluor albus is a common condition that often occurs in women, where vaginal discharge is a form of discharge from the vagina but not blood. Although it is often considered normal, vaginal discharge can be a serious problem and a clinical manifestation of various types of diseases. In Indonesia, 75% of women have experienced vaginal discharge. Based on the data we got at the Kutai health center itself, 256 cases of vaginal discharge affected teenage women. Objectives. This study is to describe the relationship between knowledge and attitudes about vulva hygiene with incidence of leucorrhea in Kutai, Tangerang Community Health Center. Methods. Quantitative with descriptive correlational method with cross-sectional approach. The sample of this research is a female adolescent between 18-20 years with total of respondents are 79 female adolescents with using the total sampling technique. The instrument used is a questionnaire. The analytical method used is univariate and bivariate. Results. Based on knowledge, there are 33 respondents (41.8%) have a good level and 47 respondents (59.5%) classified as having an adequate attitude of vulva hygiene, but 71 respondents (89.9%) had experienced pathological vaginal discharge (abnormal). Statistic test regarding the relationship between the level of knowledge and attitudes of female adolescents about vulva hygiene with vaginal discharge shows results p-value: 0.057 > 0.05 for knowledge and p-value: 0.089> 0.05 for attitude so there is no relationship between the level of knowledge and attitudes of female adolescent about vulva hygiene with vaginal discharge. Conclusion. Expected for Community Health Center, especially in Kutai, Tangerang can build a program that focuses on providing counseling and education about health reproduction for female adolescents so that the incidence of pathological vaginal discharge can be reduced